B, N Dual Doped Coral-Like Carbon Framework With Superior Pseudocapacitance and Surface Wettability - Han, Lu; Chen, Xu; Zeng, Shijie; Liu, Jia; Yang, Zhongli; Wang, Zhiqiang; Li, Liang; Wang, Haibao; Hou, Zhanbin; Xu, Min (Frontiers in Materials, 2021)
For carbon-based materials have been widely used for supercapacitors (SCs), rational fabrication and surface structure design of carbon-based materials with high supercapacitive capacity and excellent cycling stability are of significant importance. The bio-inspired coral-like porous carbon structure has attracted much attention recently in that it can offer large surface area for ion accommodation and favor the diffusion of electrolyte ions, hence improving the energy storage capacity. Herein, we designed a superiorly hydrophilic B, N dual doped coral-like carbon framework (BN-CCF) and studied its surface wettability via low-field nuclear magnetic resonance relaxation technique. The unique coral-like micro-nano structure and B, N dual doping can enhance the pseudocapacitance and improve the surface wettability. Therefore, when used as electrodes of SCs, the BN-CCF displays a high specific capacitance of 457.5 F g-1 at 0.5 A g-1, high capacitance retention of 66.1% even when the current density increases 20 folds and excellent cycling stability of nearly 100% after 10000 cycles in 1 M H2SO4 aqueous electrolyte. The symmetrical SCs assembled by BN-CCF electrodes shows a high energy density of 14.92 Wh kg-1 at the power density of 600 W kg-1. The strategy in this work provides an effective way to improve the performance of carbon-based SCs via simple structural regulation of carbons